Analysis on the Multi-Constellation SBAS Performance of SDCM in Korea - Lim, Cheol-Soon; Park, Byungwoon; So, Hyoungmin; Jang, Jaegyu; Seo, Seungwoo; Park, Junpyo; Bu, Sung-Chun; Lee, Chul-Soo (Journal of Positioning Navigation and Timing, 2016)
A Satellite Based Augmentation System (SBAS) provides differential correction and integrity information through geostationary satellite to users in order to reduce Global Navigation Satellite System (GNSS)-related errors such as ionospheric delay and tropospheric delay, and satellite orbit and clock errors and calculate a protection level of the calculated location. A SBAS is a system, which has been set as an international standard by the International Civilian Aviation Organization (ICAO) to be utilized for safe operation of aircrafts. Currently, the Wide Area Augmentation System (WAAS) in the USA, the European Geostationary Navigation Overlay Service (EGNOS) in Europe, MTSAT Satellite Augmentation System (MSAS) in Japan, and GPS-Aided Geo Augmented Navigation (GAGAN) are operated. The System for Differential Correction and Monitoring (SDCM) in Russia is now under construction and testing. All SBASs that are currently under operation including the WAAS in the USA provide correction and integrity information about the Global Positioning System (GPS) whereas the SDCM in Russia that started SBAS-related test services in Russia in recent years provides correction and integrity information about not only the GPS but also the GLONASS. Currently, LUCH-5A(PRN 140), LUCH-5B(PRN 125), and LUCH-5V(PRN 141) are assigned and used as geostationary satellites for the SDCM. Among them, PRN 140 satellite is now broadcasting SBAS test messages for SDCM test services. In particular, since messages broadcast by PRN 140 satellite are received in Korea as well, performance analysis on GPS/GLONASS Multi-Constellation SBAS using the SDCM can be possible. The present paper generated correction and integrity information about GPS and GLONASS using SDCM messages broadcast by the PRN 140 satellite, and performed analysis on GPS/GLONASS Multi-Constellation SBAS performance and APV-I availability by applying GPS and GLONASS observation data received from multiple reference stations, which were operated in the National Geographic Information Institute (NGII) for performance analysis on GPS/GLONASS Multi-Constellation SBAS according to user locations inside South Korea utilizing the above-calculated information. KCI Citation Count: 1